(untitled) (Agro Productividad, 2022)
O Objective: To identify the use of traditional food, quantify the main foods consumed in the region, and propose a dish of good eating for the Totonac region. Methodology: A semi-structured survey was carried out in 328 households of the municipality of Filomeno Mata, Veracruz, Mexico. The Household Dietary Diversity Score (HDDS) and a section were used to obtain information about the regional foods that the local population consumes on a daily basis. Results: The families recognized a total of 35 regionally-produced vegetal and animal products. Each household that participated in the survey mentioned an average of 7 foods out of the whole list. Limitations: To improve and implement a good food dish, several elements must be taken into account: age, gender, height, physical activity, or physiological condition, among others. Conclusions: The registered foods are linked to the local culture and open a door to the generation of various resource-leveraging strategies, such as the dish of good eating for the Totonac region.